2020
DOI: 10.1097/md.0000000000018831
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes distress, happiness, and its associated factors among type 2 diabetes mellitus patients with different therapies

Abstract: This study aimed to investigate diabetes distress, happiness, and its associated factors of patients with type 2 diabetes mellitus (T2DM) treated by different therapies, and to analyze the related impact factors. A total of 1512 patients with T2DM were randomly selected from 18 tertiary hospitals in Hunan province from January 2016 to April 2016 who has been treated with oral antidiabetics monotherapy, insulin monotherapy, and combination therapy. Use the general information questionnaire, WHO-5 (the World Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This finding was consistent with the results of prior studies. 39 , 47 , 48 However, some studies have found no association between having diabetic complications and DRD. 13 , 20 , 49 In contrast to previous studies, lower education level was a major factor for high diabetes distress scores in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with the results of prior studies. 39 , 47 , 48 However, some studies have found no association between having diabetic complications and DRD. 13 , 20 , 49 In contrast to previous studies, lower education level was a major factor for high diabetes distress scores in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Saatci et al demonstrated that treatment satisfaction is associated with the general wellbeing of a person with T2DM [ 37 ]. Other studies have shown that the happiness of persons with diabetes is associated with physical activity and mindfulness training, which were not explored in the present survey [ 15 , 16 ]. In addition, although the dietary intake and social behavior of persons with T2DM may also affect their glycemic happiness [ 15 ], these aspects were not covered in our survey.…”
Section: Discussionmentioning
confidence: 96%
“…Although the effect of the type of therapeutic interventions on the happiness of individuals with diabetes is beyond the scope of the present survey, previous studies have shown that the happiness of persons with diabetes varies with the type of intervention. Generally, insulin users have lower happiness than noninsulin users [ 15 , 29 ]. Rather than the type of treatment, our survey revealed that treatment convenience and flexibility were positively associated with glycemic happiness of persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor specific to diabetes that may explain why PPWB was not associated with physical activity among people with diabetes is diabetes distress, which has been found to be linked with PPWB (Beverly et al, 2021;Chan et al, 2020;Liu et al, 2020) and physical activity (Fisher et al, 2010;Fisher et al, 2014). Although the present study controlled for psychological distress, it did not account for diabetes distress, which differs in that the experienced emotional distress is specific to the burden of living with and managing diabetes, in addition to the interpersonal distress related to living with diabetes (Jones et al, 2015).…”
Section: Ppwb and Physical Activity Among People With Diabetesmentioning
confidence: 78%